The evaluation of higher education, cases of international institutional evaluation in Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2020)
Given the importance of evaluation, this article contextualizes the academic quality evaluation of within the field of national evaluation. Before offering practical experience in the development of evaluation processes of two public universities in Costa Rica, this article establishes a theoretical conceptual approach to the term of academic quality and to the evaluative approach developed around it. The article exposes the need to develop evaluation processes to establish coherence between the educational model of the university and the execution and results of the curricula of their careers. The article mentions types of academic quality evaluation, particularities that characterize these processes, and exposes two evaluation cases that have been developed in the country at the institutional level.
Keywords: evaluation; academic quality; academic excellence; higher education; educational model; institutional evaluation